Adsorption of Ammonium Ion from Tofu Industrial Liquid Waste by Coconut Shell-Activated Carbon - Adha, C. N.; Istiqomah, U.; Safitri, A. W.; Tarmini, T. (Indonesian Journal of Chemistry and Environment, 2019)
Liquid waste from tofu industry will flow or discharge into water. It causes pollution which is characterized by unpleasant odor. If this continues, it can damage the environment and threaten the health of the people who inhale the unpleasant odor. Activated carbon is a carbon that is able to adsorb in the liquid phase or gas phase.Â  Activated carbon is the best adsorbent in the adsorption system. The material for activated carbon comes from animals, plants, and waste or minerals that contain carbon. Coconut shell is an ingredient that can be made into activated carbon. Activated carbon from coconut shell has many benefits one of them can adsorb liquid waste from tofu industry. This study aims to examine the ability of coconut shell to adsorben, that have been activated by K2CO3 or HCl activator. In this study given the variation of activated charcoal mass and contact time variations to determine the effect on the ability of activated coconut shell charcoal adsorption on ammonia content in Liquid waste from tofu industry. The results of this study are the greater the mass of activated charcoal and the longer the contact time, the greater the ammonia absorbed by activated charcoal, which indicates that the percent decrease in ammonia concentration is greater